it will be c
as
negative with negative erased together
We find the base of the rectangles by taking the difference between the interval endpoints, and dividing by 2.
Base of rectangle = (6 - 2) / 2
= 2
The area of the first rectangle:
(4 - 2)f(4) = 2[4 + cos(4π)]
The area the second triangle:
(6 - 4)f(6) = 2[6 + cos(6π)]
Now just compute the two areas and combined them. That will give you the estimated under the curve.
To evaluate the midpoint of each rectangle, we take the midpoint of the base lengths of each rectangle. This midpoint is the x value. Then evaluate the function at that x value.
The midpoint of the first rectangle is x=3. Evaluate f(3).
The midpoint of the second rectangle is x=5. Evaluate f(5).
Answer:
(-5,3)
Step-by-step explanation:
The point (5,7) translated down 4 units gets to the point (5,3). If you reflect it over the y-axis, the x-coordinate becomes negative, and the y-coordinate stays the same. This gets you the point (-5,3)
Hope it helps and is correct!
Answer:
k = g + a
Step-by-step explanation:
g = k - a ( add a to both sides )
g + a = k , that is
k = g + a